Prevalence of Multiple Sclerosis in Vitiligo Patients and Their First-Degree Relatives: Two Diseases with Similarities in Pathogenesis and Treatment - Kavyani, Mohammadreza; Lajevardi, Vahideh; Ghiasi, Maryam; Daneshpazhooh, Maryam; Heidari, Sama; Teimourpour, Amir; Balighi, Kamran (Dermatology Practical & Conceptual, 2024)
Introduction: Vitiligo is a common pigmentation disorder manifested by white macules and patches. It is accompanied by some autoimmune and neurological diseases. Recently, it has been suggested that multiple sclerosis (MS) is more common in vitiligo patients and that they have a higher risk of developing MS during their lifetime. Objectives: In this study, we aimed to determine the prevalence of MS in patients with vitiligo and their first-degree relatives and compare it with the prevalence in the population. Methods: In this cross-sectional study, data were consecutively collected from patients referred to Razi Hospital from March 2020 to December 2021. Results: 709 patients with vitiligo participated in this study, and 15 reported a history of MS (2.12%, 95% CI: 1.06-3.17%). This rate was significantly higher than the prevalence of MS in the average population of Tehran (p < 0.001). Of the 2886 first-degree relatives of the patients, 10 had MS (0.35%, 95% CI: 0.13-0.56%), which was higher than the prevalence of MS, yet not statistically significant. Conclusions: A significant association between vitiligo and MS was observed, which should be of clinical and therapeutic importance. However, the prevalence of MS in first-degree relatives of vitiligo patients was higher than the average rate, yet not statistically significant.